ANALISIS HUKUM ISLAM DALAM PERKARA KUMULASI ISBAT NIKAH DAN CERAI GUGAT (STUDI PUTUSAN NOMOR: 0369/PDT.G/2021/PA.BKS.) - Habibi, Adam Firdaus; Suprihatin, Suprihatin; Tsaqib Idary, Muhammad (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2024)
The enactment of Law No. 1 of 1974 concerning Marriage and all its requirements has led to new issues, including "Nikah Siri." Nikah Siri refers to a marriage conducted secretly or, in other words, a marriage not registered according to the provisions of the Marriage Law. An exciting provision to examine in Law No. 1 of 1974 is Article 2, paragraph (2): "Every marriage shall be registered according to the applicable laws and regulations." However, this law still leaves room for debate because many married people still need to register their marriages with the Marriage Registrar (PPN) at the Office of Religious Affairs. In the decision 0369/Pdt.G/2021/PA.Bks, the Plaintiff filed for the legalization of Marriage to proceed with a divorce from the Defendant. From the perspective of Islamic Law, this legalization is based on the principle of "mashlahah mursalah," meaning for the common good. Meanwhile, the divorce is considered for the mutual benefit of both parties. This study examines the decision of the Bekasi Religious Court, focusing on the cumulative case of marriage legalization and divorce suit Number 0369/Pdt.G/2021/PA.Bks. In this decision, the Bekasi Religious Court's Panel of Judges granted the request for marriage legalization and divorce suit because the Marriage fulfilled Islamic legal requirements and there were no obstacles to Marriage or divorce according to Law No. 1 of 1974 in conjunction with amended Law No. 16 of 2019. The judges' effort in granting marriage legalization is considered a form of leniency (rukhsah) while granting the divorce is for both parties benefit.